CGIAR Climate Action Program in Sri Lanka - Jeya Raj, Renuka; Alahacoon, Niranga; Amarnath, Giriraj (International Water Management Institute, 2025)
The Launch of Climate Action Sri Lanka convened key stakeholders to discuss the country’s escalating climate risks, emerging policy priorities, and the strategic role of CGIAR’s Climate Action Program. The workshop aimed to refine national implementation pathways, promote cross-sectoral collaboration, and align climate initiatives with Sri Lanka’s development agenda. During the panel discussion, panel emphasized that although coordination is repeatedly recognized as essential, mechanisms often fade over time, leading to fragmented efforts. With more actors entering the climate space, a sustained and structured coordination system is urgently needed to enable proactive, anticipatory action rather than reactive responses. Group discussions highlighted several priority areas. Group 1 stressed the progress in early warning systems but called for more localized, impact-based forecasting and stronger data integration. Group 2 underscored Locally Led Adaptation as a vital approach, noting the need to overcome capacity, financial, and inclusion barriers. Group 3 emphasized integrated water–agriculture management and the importance of scalable, farmer-centred solutions. Group 4 highlighted the need for coherent policies, enhanced institutional capacity, and improved access to climate finance to drive long-term resilience. The workshop serves as a catalytic platform to refine country-level implementation pathways, strengthen cross-sectoral collaboration, and align efforts with Sri Lanka’s development and climate priorities.